2020
DOI: 10.52158/jasens.v1i02.141
|View full text |Cite
|
Sign up to set email alerts
|

Antarmuka Mikrokontroller IoT (ESP32) Dengan USB Host max3421e

Abstract: Electronic equipment made using old technology or electronic equipment in the entry-level category has not been supported by networking equipment, so for the data communication process, the microcontroller requires interfacing facilities that are in accordance with the electronic equipment used, such as a USB port. With the microcontroller that supports IoT, it allows electronic equipment to communicate over the network. An IoT microcontroller such as the ESP32 is equipped with a WiFi feature but is not equipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The block diagram of the system carried out is shown in Figure 1: Figure 1 describes the block diagram of the system as a whole including the research that has been done [5] (blue box). This ongoing research is only limited to data communication from a computer or smartphone to a USB Host max3421e (green box).…”
Section: System Block Diagrammentioning
confidence: 99%
See 2 more Smart Citations
“…The block diagram of the system carried out is shown in Figure 1: Figure 1 describes the block diagram of the system as a whole including the research that has been done [5] (blue box). This ongoing research is only limited to data communication from a computer or smartphone to a USB Host max3421e (green box).…”
Section: System Block Diagrammentioning
confidence: 99%
“…The existing solution begins with the creation of an IoT microcontroller interface prototype (ESP32) with a USB Host max3421e by utilizing the SPI protocol that has been implemented. It was found that the IoT microcontroller (ESP32) and USB Host max3421e can communicate well and are able to recognize USB devices completely as well as USB devices connected to computers [5]. By utilizing the existing WiFi facilities on the IoT microcontroller (ESP32) [6], it is hoped that the prototype will not only be able to recognize a connected USB device, but also function as a data processor and sender from a computer or smartphone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pada skripsi ini akan dirancang sebuah sistem yang menggunakan inputan dari sensor DHT22. DHT22 diklaim memiliki kualitas pambacaan yang baik, dinilai dari respon proses akuisisi data yang cepat dan ukurannya yg minimalis, serta dengan harga yang relatif murah jika dibandingkan dengan alat thermohygromoeter [4] dan RTC dapat menyimpan data waktu secara real time [5]- [7] melalui proses hitung waktu dilakukan output datanya langsung disimpan atau bisa dikirim ke device lain melalui sistem I2C [8]- [11], untuk membaca waktu dari kandang agar bisa mengetahui waktu panen jangkrik. Data dari inputannya akan diolah oleh ESP32 yang berupa System on Chip dengan Wi-Fi dan Bluetooth [12]- [16].…”
unclassified